Invasive and non-invasive brain stimulation for treatment of neuropathic pain in patients with spinal cord injury: A review. (January 2014) - Nardone, Raffaele; Höller, Yvonne; Leis, Stefan; Höller, Peter; Thon, Natasha; Thomschewski, Aljoscha; Golaszewski, Stefan; Brigo, Francesco; Trinka, Eugen
Abstract : Context: Past evidence has shown that invasive and non-invasive brain stimulation may be effective for relieving central pain. Objective: To perform a topical review of the literature on brain neurostimulation techniques in patients with chronic neuropathic pain due to traumatic spinal cord injury (SCI) and to assess the current evidence for their therapeutic efficacy. Methods: A MEDLINE search was performed using following terms: "Spinal cord injury", "Neuropathic pain", "Brain stimulation", "Deep brain stimulation" (DBS), "Motor cortex stimulation" (MCS), "Transcranial magnetic stimulation" (TMS), "Transcranial direct current stimulation" (tDCS), "Cranial electrotherapy stimulation" (CES). Results: Invasive neurostimulation therapies, in particular DBS and epidural MCS, have shown promise as treatments for neuropathic and phantom limb pain. However, the long-term efficacy of DBS is low, while MCS has a relatively higher potential with lesser complications that DBS. Among the non-invasive techniques, there is accumulating evidence that repetitive TMS can produce analgesic effects in healthy subjects undergoing laboratory-induced pain and in chronic pain conditions of various etiologies, at least partially and transiently. Another very safe technique of non-invasive brain stimulation – tDCS – applied over the sensory-motor cortex has been reported to decrease pain sensation and increase pain threshold in healthy subjects. CES has also proved to be effective in managing some types of pain, including neuropathic pain in subjects with SCI. Conclusion: A number of studies have begun to use non-invasive neuromodulatory techniques therapeutically to relieve neuropathic pain and phantom phenomena in patients with SCI. However, further studies are warranted to corroborate the early findings and confirm different targets and stimulation paradigms. The utility of these protocols in combination with pharmacological approaches should also be explored.